Synergistic Effects of Thidiazuron (TDZ) and Naphthalene Acetic Acid on Protocorm Multiplication of Dendrobium spectabile - Yenni Anisah Putri (CV. HEI PUBLISHING INDONESIA, 2025)
This study addresses the urgent need for an efficient micropropagation protocol for the endangered endemic orchid Dendrobium spectabile by optimizing protocorm multiplication for conservation purposes. Protocorms were cultured on a modified Murashige and Skoog (MS) medium using a factorial completely randomized design to evaluate four concentrations of thidiazuron (TDZ; 0.0–1.5 mg L⁻¹) and three concentrations of naphthalene acetic acid (NAA; 0.0–0.2 mg L⁻¹) during a 12-week incubation period. Statistical analysis revealed a highly significant synergistic interaction between TDZ and NAA (p = 0.003). The optimal treatment combination, consisting of 1.0 mg L⁻¹ TDZ and 0.1 mg L⁻¹ NAA, resulted in the highest protocorm multiplication rate, producing an average of 9.2 new protocorms per explant, along with a high survival rate (>95%) and superior morphological quality. This optimized protocol exhibited a 50–80% higher efficiency compared to conventional BAP-based methods, indicating that a precise TDZ–NAA ratio is essential for promoting cell proliferation while minimizing physiological disorders such as hyperhydricity. Overall, this study provides a robust and significantly improved protocol for the ex situ mass propagation and conservation of D. spectabile.